SIMULATION-BASED OPTIMIZATION FOR RESOURCE ALLOCATION AT TPL SYSTEMS - Pan, Yanchun; Zhou, Ming; Chen, Zhimin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
<span style="font-size: 10pt; font-family: "Times New Roman"; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">Allocating resource at TPL systems differs significantly from traditional private logistics systems. The resources are considered commodities sold to customers of different types. Total yield suffers when over-allocate to lower-rate or price-sensitive customers; but the resource become “spoiled” when reserve too much for full-rate or time-<span style="font-size: 10pt; font-family: "Times New Roman"; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">sensitive customers that do not arrive as expected. U<span style="font-size: 10pt; font-family: "Times New Roman"; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">ncertain order characteristics make the optimization of such decisions very hard, if not impossible. In this paper we proposed a simulation-based optimization to address related issues. A genetic algorithm based optimization module is developed to generate/search good solutions; and a discrete-event simulation model is<span style="font-size: 10pt; font-family: "Times New Roman"; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US"> created to evaluate the solutions generated. The two modules are integrated to work in evolutionary cycles to achieve the optimization. The study also compared GA/Simulation model with more traditional approach such as response surface methodology via designed experiments. The models were validated through experimental a<span style="font-size: 10pt; font-family: "Times New Roman"; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">nalysis.